THE BRAND PERSONALITY DETERMINING FACTOR OF POCARY SWAT ISOTONIC DRINK - Supri Yanto (JOURNAL OF BUSINESS STUDIES, 2020)
This research aims to analyze the brand personality determining factor in 3 variables, those are brand Trust, brand experiences, and the origin area. Because it is important for marketing managers to find factors that build brand personality to make its products can compete. The population in this study were students of business administration institution business and informatic Kwi Kian Gie with a sample of 100 respondents. The sampling technique used is probability sampling with a random sampling method. The result of this research shows that from the analysis of 3 variables and each indicator, there is one indicator that is selected to be turn out. The results of the factor analysis indicated brand experiences a major factor determining the next brand personality brand trust and region of origin. The conclusion of this study is based on test results conducted factor analysis it can be concluded that the factor of brand trust, brand experience, promotion, and place of origin become significant factors that led to the formation of Brand Personality. Where these four factors accounted for 72.721% in predicting Brand Personality, while the remaining 27.279% is the influence of other factors that are not observed in this study. Keywords: Brand’s Personality, Brand’s Trust, Brand’s Experience.